TINJAUAN YURIDIS TERHADAP PENEGAKAN HUKUM BAGI PENGENDARA KENDARAAN BERMOTOR YANG TIDAK MEMBAYAR PAJAK - Yudi Rusyadi; Ujang Bahar; Achmad Jaka Santos Adiwijaya (JURNAL ILMIAH LIVING LAW, 2020)
Increasing the ownership of motorized motorists will also increase the number of taxpayers who must pay taxes. But not a few taxpayers who later neglect the payment of the tax. This study aims to determine and analyze law enforcement and the effectiveness of fines sanctions for motorized motorists who do not pay taxes based on Law Number 22 the Year 2009 concerning Traffic and Road Transportation. The research method used in this study is normative juridical research. Law enforcement of motorized motorists who do not pay taxes based on Law Number 22 the Year 2009 concerning Road Traffic and Transport, sanctions imposed on taxpayers, first warning efforts are made in the form of notification of Motor Vehicle Tax (PKB) and late notice PKB payment. Then if the taxpayer has not appropriately responded, administrative sanctions will be in the form of fines and interest. The implementation of administrative sanctions in the form is considered less effective.